2010
DOI: 10.1007/s11199-010-9894-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Body Image in Males and Females: Contemporary Issues and Future Directions

Abstract: Research presented in this special issue focuses on a number of key contemporary themes relating to gendered body image. This paper considers what these studies tell us about the associations between body image and self-esteem, internalization of thin/muscular ideals, social comparison, and social identity and makes suggestions for interventions to improve body image in girls/ women and boys/men. It is concluded that psycho-social interventions to reduce internalization, to make social comparison processes mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 55 publications
2
61
1
12
Order By: Relevance
“…For seventh-and eighth-grade boys, Smolak and Stein (2006) found that the interaction of exposure to muscular images in magazines and being invested in their physical strength predicted boys' drive for muscularity. In a review of factors associated with body image in boys, men, girls, and women, Grogan (2010) identified social-and gender-identity as factors that influence boys' investment in societal appearance norms. In a related study, Smolak and Stein (2010) found that boys' investment in male physical attributes (e.g., strength) predicted investment in media images of men who have the muscular and lean body ideal seven months later.…”
Section: Sociocultural Weight Pressuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For seventh-and eighth-grade boys, Smolak and Stein (2006) found that the interaction of exposure to muscular images in magazines and being invested in their physical strength predicted boys' drive for muscularity. In a review of factors associated with body image in boys, men, girls, and women, Grogan (2010) identified social-and gender-identity as factors that influence boys' investment in societal appearance norms. In a related study, Smolak and Stein (2010) found that boys' investment in male physical attributes (e.g., strength) predicted investment in media images of men who have the muscular and lean body ideal seven months later.…”
Section: Sociocultural Weight Pressuresmentioning
confidence: 99%
“…In a related study, Smolak and Stein (2010) found that boys' investment in male physical attributes (e.g., strength) predicted investment in media images of men who have the muscular and lean body ideal seven months later. Researchers (e.g., Choma et al, 2010;Grogan 2010;Pompper, 2010) have suggested that the media's focus on male physical appearance may lead boys and men to feel valued for how they look more so than for who they are or what they can do, leading to a sense of objectification (Strelan & Hargreaves, 2005).…”
Section: Sociocultural Weight Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research findings (e.g., Grogan, 2010;Ricciardelli & McCabe, 2011) have suggested that boys do engage in social body comparisons, and such comparisons are indirectly associated with body dissatisfaction though internalization of societal appearance standards.…”
Section: Social Body Comparisons and Internalizationmentioning
confidence: 99%
“…Recently, researchers have recommended to shift the research focus towards examining potential protective and buffering factors that may explain why some women do not report or experience body image concern (Grogan, 2010) The present study sought to investigate dispositional mindfulness as a protective factor within this field of research, hypothesizing that women reporting higher levels of dispositional mindfulness will also report significantly less negative appearance evaluation, investment in appearance, preoccupation with weight, shame and psychological distress and higher self-esteem in comparison to women reporting lower levels of dispositional mindfulness.…”
Section: The Current Investigationmentioning
confidence: 99%